To the problem of personal history study Krasnodar employees pedagogical institute - Oleg V. Matveyev (Кавказология)
The author researches the personal history of the Krasnodar Pedagogical Institute, turning to the example of its director I.N. Bagov in 1935–1937. Relied upon by the party documents, the author shows the director efforts to manage the educational life of the university, difficult relationships with colleagues in the atmosphere of universal suspicion and denunciations, the desire to preserve professional personnel, and save students and teachers. Through the mirror of party documents, the actions of the director of the Institute for Improving the Life and Culture of Students, the level of research work of the university, the fight against laziness and mismanagement are traced. From ideologically biased texts, I.N. Bagov’s human traits, through the assessments of people guided by both political and personal motives in the conditions of a nationwide atmosphere of suspicion. The author shows the feasibility of applying the contextual approach, when the historical biography acts simultaneously as the reconstruction of the unique fate of the university’s 1930s head, as well as a vehicle for knowing the historical society in which he acted. Ibrahim Nagozhevich Bagov shared with his people both the bright pages of his dramatic story, associated with the construction of new life and good expectations, and hardship that fell into the country and society in that conflicting era. The author believes that a considerable part of the work by the director I.N. Bagov contributed to the successes achieved by Kuban and Adygea in the prewar years in the training of qualified specialists for public education and economic work.